TiN-nanorod-coated carbon fiber cathode for high-current-density electron emission. (April 2019) - Li, Limin; Fu, Songling; Huang, Xiuxiang; Tang, Qiang; Peng, Ke; Li, Zhongyang
Abstract: The challenges confronting high-current cold cathodes stimulate the development of robust cathode materials with low emission threshold and high field enhancement factor. In this paper, we prepared a TiN nanorod/carbon fiber composite cathode by hydrothermal method and nitriding. The light emission and plasma formation on the cathode surface were compared between carbon fiber cathode and TiN nanorod/cabon fiber cathode. The turn-on times of TiN nanorod/cabon fiber cathode and carbon fiber cathode were 12 ns and 31 ns, respectively, showing a faster turn-on of TiN nanorod/cabon fiber cathode, which was supported by theoretical derivation, developing process of emission area and IV Characteristics. The emission thresholds of TiN nanorod/cabon fiber cathode and carbon fiber cathode were around 0.4 kV/cm and 0.8 kV/cm, respectively, and such a lower emission threshold of TiN nanorod/cabon fiber cathode enables the uniform and large-area plasma generated on cathode surface. As a whole, TiN nanorod/cabon fiber cathode represents a promising cold cathode with superior performances. Highlights: A TiN nanorod/carbon fiber composit cathode was prepared by hydrothermal method and nitriding. The uniform and large-area plasma was generated on TiN nanorod/cabon fiber cathode. TiN nanorod/cabon fiber cathode turned on faster, and had a lower emission threshold.